Molecular epidemiology of methicillin-resistant Staphylococcus aureus from different population groups in Argentina. (December 2020) - Moreno Mochi, P.; Vargas, J.M.; Vivaldo, S.; Bottiglieri, M.; López, C.; Mochi, S.; Cobos, M.; Castillo, M.; del Campo, R.; Jure, M.A.
Highlights: Molecular epidemiology of methicillin-resistant Staphylococcus aureus (MRSA) in a multiborder area of Argentina. The prevalent staphylococcal cassette chromosome mec type was SCC mec IV. The Cordobes/Chilean epidemic clone was not detected in the present MRSA collection. ST5 was the most prevalent in colonisation, community and invasive settings. Abstract: Objectives: In Latin America, methicillin-resistant Staphylococcus aureus (MRSA) is a leading cause of nosocomial infections. Limited studies have addressed the molecular epidemiology of MRSA clones in Argentina, characterised by continuous human migratory movements. The aim of this study was to describe the MRSA epidemiology, including distinct patient populations from different regions of the country. Methods: MRSA strains were collected in epidemiological studies conducted from 2009 to 2015 in three cities (Formosa, Córdoba and Tucumán) and involving four population groups: community adult patients; hospitalised adults; hospitalised children; and healthy children (nasal colonisation). Antimicrobial susceptibility testing, SCC mec and Panton–Valentine leukocidin (PVL) typing, pulsed-field gel electrophoresis (PFGE) and multilocus sequence typing (MLST) were performed. Results: A total of 120 MRSA isolates were recovered with an important population diversity in the groups studied; in community adult patients, MRSA isolates corresponded to ST5, ST267 and ST1619; from hospitalised adults they were ST97, ST5, ST72, ST125, ST200, ST647, ST747, ST935 and ST2941; from hospitalised children they were ST5, ST30, ST34, ST1163 and ST1619; and from colonised children they were ST5, ST125, ST34, ST100, ST1619, ST207 and ST1163. Results of SCC mec typing showed SCC mec I, SCC mec IIIA, SCC mec IV and SCC mec ND associated or not with PVL genes. Conclusions: MRSA genetic lineages have differing distribution in the three regions. The most prevalent was ST5 in colonisation, community and invasive settings. Here we describe ST34-SCC mec IV clone for the first time in the hospitalised paediatric population. These findings contribute to the understanding of epidemiological changes in recent years.